Bow-Tie Diagrams for Risk Management in Anaesthesia. Issue 6 (November 2016) - Culwick, M. D.; Merry, A. F.; Clarke, D. M.; Taraporewalla, K. J.; Gibbs, N. M.
Bow-tie analysis is a risk analysis and management tool that has been readily adopted into routine practice in many high reliability industries such as engineering, aviation and emergency services. However, it has received little exposure so far in healthcare. Nevertheless, its simplicity, versatility, and pictorial display may have benefits for the analysis of a range of healthcare risks, including complex and multiple risks and their interactions. Bow-tie diagrams are a combination of a fault tree and an event tree, which when combined take the shape of a bow tie. Central to bow-tie methodology is the concept of an undesired or 'Top Event', which occurs if a hazard progresses past all prevention controls. Top Events may also occasionally occur idiosyncratically. Irrespective of the cause of a Top Event, mitigation and recovery controls may influence the outcome. Hence the relationship of hazard to outcome can be viewed in one diagram along with possible causal sequences or accident trajectories. Potential uses for bow-tie diagrams in anaesthesia risk management include improved understanding of anaesthesia hazards and risks, pre-emptive identification of absent or inadequate hazard controls, investigation of clinical incidents, teaching anaesthesia risk management, and demonstrating risk management strategies to third parties when required.